2011
DOI: 10.1038/onc.2011.410
|View full text |Cite
|
Sign up to set email alerts
|

Mucin 1 enhances the tumor angiogenic response by activation of the AKT signaling pathway

Abstract: Although the hyper-glycosylated transmembrane protein Mucin 1 (MUC1) is aberrantly overexpressed in human breast carcinoma, the biological significance of MUC1 overexpression is unclear. This study showed that MUC1 expression promoted the synthesis and secretion of vascular endothelial growth factor (VEGF) through the AKT signaling pathway. Increase VEGF production through MUC1 expression had a number of effect. First, MUC1 transfection increased expression of VEGF in breast cancer cells. Second, MUC1-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 53 publications
2
48
0
Order By: Relevance
“…77 Though MUC1 is a transcriptional target of HIF1-α as discussed above, MUC1 also interacts with HIF1-α in the cytoplasm and promotes transcriptional upregulation of HIF1-α targets such as leptin, TGFβ3 and VEGF. [78][79][80] Furthermore, MUC1 and VEGF expression correlate in human breast cancer cell lines, and MMTV-PyMT mice expressing human MUC1 display more angiogenesis than MMTV-PyMT mice on a Muc1 null background, 81 further supporting a role for MUC1 in the onset of angiogenesis.…”
Section: Mechanism Of Overexpressionmentioning
confidence: 87%
“…77 Though MUC1 is a transcriptional target of HIF1-α as discussed above, MUC1 also interacts with HIF1-α in the cytoplasm and promotes transcriptional upregulation of HIF1-α targets such as leptin, TGFβ3 and VEGF. [78][79][80] Furthermore, MUC1 and VEGF expression correlate in human breast cancer cell lines, and MMTV-PyMT mice expressing human MUC1 display more angiogenesis than MMTV-PyMT mice on a Muc1 null background, 81 further supporting a role for MUC1 in the onset of angiogenesis.…”
Section: Mechanism Of Overexpressionmentioning
confidence: 87%
“…The glycosylated extracellular domain of MUC1 inhibits anoikis by shielding death receptors such as the Fas ligand on the cell surface [125]. MUC1 enhances carcinogenesis by activation of the Akt pathway that regulates cell proliferation and migration [149,150]. Activation of the MUC1 cytoplasmic tail leads to the phosphorylation of Akt and Bad, resulting in the upregulation of mitochondrial Bcl-Xl and inhibition of apoptosis [132,151].…”
Section: Contribution Of Mucins To Carcinogenesis and Metastasismentioning
confidence: 99%
“…Another protein to mention is MUC1, a hyperglycosylated transmembrane protein expressed on normal secretory epithelial cells, while 90% of carcinomas show aberrant MUC1 expression (12,13). Preclinical models have demonstrated that MUC1 overexpression can stimulate VEGF synthesis and secretion through activation of the AKT signaling pathway (12) and can contribute to hypoxia-driven angiogenesis (13).…”
Section: Introductionmentioning
confidence: 99%